PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI - Oktaviani, Retno Fuji; Indrabudiman, Amir; Niazi, Hakam Ali (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- This research aims to analyze the dynamic correlation by using stock prices daily data of 6 ASEAN equity markets during the period of 2007 until 2017 and then try to analyze the interdependence between equity markets.Design/methodology/approach- The sample research method uses a purposive sampling technique with a total sample of 14 companies that meet the criteria. The statistical analysis used is SEM PLS.Findings- This research provides information and consideration for management to pay more attention to CSR, GCG activities and company performance. The greater the value of financial performance, the value of the company declared better. CSR disclosure can not only improve the company's image in the eyes of stakeholders, but CSR disclosure has become a global issue that receives wide attention.Implications- The result shows that the interdependence between ASEAN 6 stock market seems still in high volatility, and the progress of correlation between the stock market did not have any significant leap as expected from the ASEAN Economic Community. Keywords: Financial Performance, Corporate Social Responsibility, Good Corporate Governance, Company Value